2015
DOI: 10.1038/srep07997
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic doping as a source for robust ferromagnetism at the interface between antiferromagnetic cobalt oxides

Abstract: Polar oxide interfaces are an important focus of research due to their novel functionality which is not available in the bulk constituents. So far, research has focused mainly on heterointerfaces derived from the perovskite structure. It is important to extend our understanding of electronic reconstruction phenomena to a broader class of materials and structure types. Here we report from high-resolution transmission electron microscopy and quantitative magnetometry a robust – above room temperature (Curie temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 35 publications
6
24
1
Order By: Relevance
“…These observations are in agreement with what has been found also at the interface of Au-Fe 3 O 4 composites [48,49], Co/Co 3 O 4 nanooctahedra [25], and Fe oxidized cubic NP [50], suggesting that lattice mismatch correlates with changes in magnetic anisotropy. There is also evidence that lattice strain induced by acoustic waves applied to some magnetic structures [51,52] can influence the value of the anisotropy constant and its easy axis.…”
Section: Magnetic Characterizationsupporting
confidence: 82%
See 2 more Smart Citations
“…These observations are in agreement with what has been found also at the interface of Au-Fe 3 O 4 composites [48,49], Co/Co 3 O 4 nanooctahedra [25], and Fe oxidized cubic NP [50], suggesting that lattice mismatch correlates with changes in magnetic anisotropy. There is also evidence that lattice strain induced by acoustic waves applied to some magnetic structures [51,52] can influence the value of the anisotropy constant and its easy axis.…”
Section: Magnetic Characterizationsupporting
confidence: 82%
“…Remarkably, although the Néel temperature of Co 3 O 4 is below 40 K, the loop shifts persist up to ∼250 K or above, demonstrating the robustness of the exchange coupling between core and shell and the persistence of EB effects up to almost room temperature. Previous reports on the EB effect in systems with coexisting Co/Co 3 O 4 phases indicated that a minor presence of CoO led to the persistence of EB much above its T N [24][25][26][27][28][29]. Analogously, persistence of EB above T N was also observed in Co/FeF 2 [56] and was explained by retention of short range magnetic ordering above T N .…”
Section: Magnetic Characterizationsupporting
confidence: 50%
See 1 more Smart Citation
“…Remarkably, although the Néel temperature of Co 3 O 4 is below 40 K, the loop shifts persist up to ∼250 K or above, demonstrating the robustness of the exchange coupling between core and shell and the persistence of EB effects up to almost room temperature. Previous reports on the EB effect in systems with coexisting Co/Co 3 O 4 phases indicated that a minor presence of CoO led to the persistence of EB much above its T N [24][25][26][27][28][29]. Analogously, persistence of EB above T N was also observed in Co/FeF 2 [56] and was explained by retention of short range magnetic ordering above T N .…”
Section: Magnetic Characterizationsupporting
confidence: 48%
“…This process can be controlled under proper synthesis conditions to * oscar@ffn.ub.es; http://www.ffn.ub.es/oscar † sspsg2@iacs.res.in prevent further oxidation, leading to the formation of core/shell structures with the oxide phase (often an AF or ferrimagnetic material [22]) usually formed at the outer part of the structures. In the case of Co NP, most of the published studies [23] report the formation of the CoO phase on the shell, although in some cases the presence of the Co 3 O 4 has also been evidenced by structural [24,25] or magnetic characterization [26], The possibility of observing EB in Co based nanostructures in contact with Co 3 O 4 has been rather less investigated and the published studies focus on layered structures [27][28][29][30][31]. Synthesis of single phase CoO or Co 3 O 4 NP have been achieved by several authors, that have reported AF magnetic behavior with ordering temperatures reduced compared to the bulk values [32][33][34] and remanence values much higher than those for the bulk due to finite-size effects [26,35].…”
Section: Introductionmentioning
confidence: 99%